Parental influences on self-esteem of early adolescents: a multiracial sample from Selangor, Malaysia - Chin, Yit Siew; Woon, Fui Chee (Community Health Society Malaysia, 2018)
Background: This cross-sectional study aims to determine the association between socio-demographic characteristics, parenting style, and self-esteem among early adolescents. Materials and Methods: A total of 716 early adolescents aged 10–11 years attending primary schools in Selangor state, Malaysia were enrolled in this study. Perceived parenting style and self-esteem were assessed through the self-administered Parenting Characteristics questionnaire and Rosenberg Self-Esteem Scale, respectively. Pearson’s product-moment correlation and one-way ANOVA were employed to determine the bivariate relationships between socio-demographic characteristics and parenting style with self-esteem. Multiple linear regression analysis was utilized to determine the factors that significantly contributed to self-esteem of the respondents. Result: The results revealed that the predominant parenting style practiced by respondents’ fathers was authoritarian (44.4%), while that by respondents’ mothers was authoritative (38.2%). Ethnicity, paternal parenting style, and maternal parenting style were significantly associated with self-esteem of the respondents in the bivariate analyses. No associations were found between age, gender, paternal and maternal educational level, monthly household income, and self-esteem. Results of the multiple linear regression model demonstrated that being Chinese (β=-0.29), being Indian (β=-0.12), authoritative father (β=0.15), authoritative mother (β=0.16), and permissive mother (β=0.13) were significantly associated with self-esteem among the respondents (R2=0.14). Conclusion: These findings suggest that being Malay, authoritative, and permissive parenting positively influenced the self-esteem of early adolescents. Further research should be conducted to assess the interaction effects between ethnicity and parenting style on self-esteem in early adolescents.